2015
DOI: 10.1093/bja/aev364
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for intensive care unit admission after bariatric surgery: a multicentre population-based cohort study

Abstract: Intensive care unit admission after bariatric surgery was uncommon (4.9% of all patients), with 30.9% of all referrals being unplanned. A nomogram and smartphone application based on five important preoperative factors may assist anaesthetists to conduct preoperative planning for high-risk bariatric surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…(12,13,16,17) Research involving 12,062 patients undergoing bariatric surgeries, of whom only 590 (4.90%) were admitted to the ICU postoperatively, showed that this group of patients had a significantly higher mean age and more frequently required an abdominal reoperation. Thus, contrary to what was verified in the present study, both groups had different characteristics, and ICU stay was better justified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(12,13,16,17) Research involving 12,062 patients undergoing bariatric surgeries, of whom only 590 (4.90%) were admitted to the ICU postoperatively, showed that this group of patients had a significantly higher mean age and more frequently required an abdominal reoperation. Thus, contrary to what was verified in the present study, both groups had different characteristics, and ICU stay was better justified.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, contrary to what was verified in the present study, both groups had different characteristics, and ICU stay was better justified. (16) A prospective Brazilian study with a sample of 120 patients submitted to laparoscopic bariatric surgery tested an index to evaluate the need for immediate hospitalization in intensive care, with no patients admitted to the ICU and no occurrence of postoperative complications. (14) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013*). ICU monitoring is recommended for those patients at high cardiopulmonary risk . Patients with left ventricular systolic dysfunction (left ventricular ejection fraction < 50%) had a slight excess in early postoperative heart failure and myocardial infarction but no excess mortality at 1 year .…”
Section: Executive Summarymentioning
confidence: 99%
“…Based on this risk score, the mortality risk is low (0·3 per cent) with one variable, intermediate (1·9 per cent) with two or three variables and high (7·6 per cent) with four or five variables. Postoperative care in a monitored setting should be planned for high‐risk obese patients (older patients, BMI at least 50 kg/m 2 , moderate to severe OSAS, metabolic syndrome, obesity hypoventilation syndrome, other major co‐morbidities), especially after major, revisional or open surgery, or when parenteral opioids, or use of CPAP or NIPPV, is anticipated after operation.…”
Section: Resultsmentioning
confidence: 99%